PENGARUH IMPLEMENTASI PP NO 23 TAHUN 2018, PEMAHAMAN PERPAJAKAN, DAN MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Vinska Kiki Anggraeni; Tirza Oktovianti Lenggono (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2021)
ABSTRACT This study aims to test empirically the effect of the implementation of PP No. 23/2018, the influence of tax understanding, and the modernization of the tax administration system on MSME taxpayer compliance. The research method in this thesis is descriptive statistical analysis, data quality test, classical assumption test, multiple regression analysis and hypothesis testing. The total population of this study consisted of 14,200 individual SME taxpayers who were registered at the Ambon Pratama Tax Office by using the sample determination using the Slovin formula obtained 100 people as the sample. The type of data used is primary data, obtained from questionnaires distributed to respondents. The results of this study prove partially the implementation of PP No. 23 of 2018 has an effect on MSME taxpayer compliance, understanding of taxation affects MSME taxpayer compliance and the modernization of the tax administration system affects MSME taxpayer compliance. Keywords : Implementation of PP No. 23 of 2018, Understanding of Taxation and Modernization of the Tax Administration System.